A preliminary report on the association between maternal serum organophosphate ester concentrations and gestational diabetes mellitus. Issue 3 (March 2023) - Jin, Hangbiao; Gao, Yu; Chen, Rongrong; Zhang, Yingying; Qu, Jianli; Bai, Xiaoxia; Zhao, Meirong
Abstract: Organophosphate esters (OPEs) are extensively manufactured and used in China. Whether exposure to OPEs during pregnancy increases the risk of gestational diabetes mellitus (GDM) is unknown. Between 2011 and 2012, a case-control study including 130 and 67 women with and without GDM, respectively, was conducted in Hangzhou, China. The levels of 10 OPEs in maternal serum samples at delivery were quantified, and the relationships between the OPE concentrations and GDM risk were investigated. The results show that in all participants, tri- n -butyl phosphate (TNBP, median: 2.02 ng/mL) was the most common OPE present in the serum, followed by tri-phenyl phosphate (TPHP, median: 1.74 ng/mL) and tri-iso-butyl phosphate (median: 1.68 ng/mL). With one-unit elevation in the tris (2-chloroethyl) phosphate, TNBP, TPHP, and tris (2-butoxy ethyl) phosphate (TBOEP) concentrations in maternal serum, 1-h glucose levels increased by 0.19 (95% confidence interval (CI): −0.01, 0.29), 0.11 (95% CI: −0.18, 0.62), 0.29 (95% CI: 0.12, 0.58), and 0.20 units (95% CI: 0.01, 0.44), respectively. In addition, a unit increase in TBOEP levels in maternal serum was associated with an increase of 0.26 units (95% CI: 0.09, 0.61) in 2-h glucose levels. After adjusting for covariate factors, serum TNBP (odds ratio (OR) = 2.07; 95% CI: 1.27, 3.41), TBOEP (OR = 2.63; 95% CI: 1.68, 4.11), and TPHP (OR = 1.03; 95% CI: 1.05, 1.51) concentrations were associated with GDM incidence in pregnant women. Overall, TNBP, TBOEP, and TPHP exposure during pregnancy is associated with GDM risk and increased glucose levels. Graphical abstract: Image 1